Effects of Dietary Zinc Bearing Palygorskite Supplementation on the Carcass Traits, Chemical Composition of Muscle, and Muscular Lead and Chromium Contents of Broilers - Weili Yang; Yueping Chen; Yefei Cheng; Xiaohan Li; Chao Wen; Yanmin Zhou (The Journal of Poultry Science, 2017)
The present study was conducted to investigate the effects of zinc (Zn) bearing palygorskite (ZnPal) inclusion on the carcass traits, chemical composition of muscle, and muscular lead (Pb) and chromium (Cr) contents of broilers. A total of 240 1-day-old Arbor Acres broiler chicks were randomly divided into 5 dietary treatments with 6 replicates of 8 chicks each. Broilers in the 5 treatments were fed a basal diet supplemented with 0 (Control group), 20, 40, 60, and 80 mg/kg Zn in the form of ZnPal for 42 days, respectively. There were no differences in the carcass yield, abdominal fat yield, subcutaneous fat thickness, and intramuscular fat width among treatments (P>0.05). Compared with the control group, the eviscerated yield (P=0.010) and thigh muscle yield (P=0.046) were quadratically increased by the supplementation of ZnPal (P<0.05). Similarly, the breast muscle yield was linearly (P=0.024) and quadratically (P=0.011) increased by ZnPal inclusion. The addition of ZnPal to diets of broilers also linearly (P=0.002) increased fat content in the thigh. Moreover, the supplementation of ZnPal linearly and quadratically reduced the content of muscular Pb and the content of Cr in the thigh muscle (P<0.05). It was concluded that ZnPal inclusion could improve carcass traits, increase fat content in the thigh, and reduce the accumulations of Pb and Cr in the muscles, and this effect was more pronounced when extra Zn dosage in the form of ZnPal was 40 mg/kg.